Effects of teaching citizenship component of social studies on primary school pupils’ civic knowledge and skills (2013)
Most Nigerians are characterized with non-conformity with democratic principles that would have brought desired transformation in the Nation. This study therefore investigated effect of teaching citizenship education component of Social Studies on primary School Pupils’ civic knowledge and skills. Two null hypotheses were formulated and tested at 0.05 level of significance. The study adopted a pretest-postest quasi experimental design. One primary school was purposively selected in Oluponna Local Government Area of Osun State using 30 pupils. Two instruments used to collect data were, “Civic knowledge and skills Test” and “Social Studies instructional guide”. The participants were exposed to treatment for seven weeks on citizenship education concepts. Data collected were analysed using t-test. The results showed that there was a significant effect of treatment on pupil civic knowledge and skill. It was also shown that there was no significant difference in civic knowledge of pupils but significant on skill based on gender. The study concluded that effective teaching of Social Studies could promote civic knowledge and development of intellectual and participatory' civic skill in primary school pupil in Nigeria.